Emotional Denial as a Self-Defense Mechanism in Daisy’s Character in Picking Daisies on Sundays - Tyana Putri Utami; Thohiriyah (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
Emotional denial is one of the psychological defense mechanisms that individuals use to cope with distressing emotions and threatening realities. This study examines emotional denial as a self-defense mechanism in Daisy’s character in the novel Picking Daisies on Sundays by Liana Cincotti. The objective is to analyze the forms of Daisy's emotional denial and explain how it functions as a self-defense mechanism. By using a qualitative descriptive method with a textual analysis approach, data were collected through close reading and documentation techniques, focusing on relevant dialogues, narrations, and character actions. The collected data were then analyzed using Sigmund Freud's psychoanalytic theory, focusing on the concept of defense mechanisms as the theoretical framework. The findings reveal that Daisy’s emotional denial manifests through verbal rejection, avoidant behavior, and minimization of conflict, triggered by internal trauma, low self-worth, and external relational threats. This study concludes that emotional denial does not operate as a single reaction, but as a structured strategy combining verbal, behaviour, and thoughts. While this mechanism temporarily protects the character’s mind, it operates maladaptively by creating a continuous loop emotional avoidance that stops her personal growth and negatively affects her relationship with Levi.